PEDAGOGICAL POTENTIAL OF APPLIED CREATIVITY MEANS OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROCESS OF TEACHING AND INFORMATIVE INTEREST OF YOUNGER SCHOOLCHILDREN - Gusev, Dmitriy; Zhestkova, Elena; Kudakova, Nataliya; Filippova, Ludmila; Podshednaya, Faina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
At the present stage to find new ways and opportunities for the development of educational - cognitive interest of the student. In the course of this search is rather difficult to overestimate the positive impact of modern information technologies in the development of the child. Digital technology is increasingly penetrating our everyday lives and are a powerful tool for development and training. However, the student is increasingly in a virtual world, and eventually the younger generation lost its national identity. Folk art in our multinational country holds a special place. It reflects the originality, poetry, simplicity and wisdom of the views of the Russian people; It brings the best features of the national character. The study of this problem is one of the objectives of our study. The article discusses the implementation of the pedagogical potential of national applied creativity by means of information and communication technologies in primary education in the process of teaching and educational interest.